AB1031 Anti-drug antibodies: assay performance in patients treated with ANTI-TNF biodrugs. (15th June 2017) - Hock, B; O'donnell, JL; Liu, J; Keating, P; Spellerberg, M; Stamp, L; Barclay, M
Abstract : Background: Minimum biodrug concentrations of ∼7mg/l are predictive of disease remission 1 . Very low/absent biodrug concentrations associate with loss of benefit which may be due to ADA 2 however the clinical utility of ADA is assay dependant. In rheumatoid arthritis the combination of low/absent drug concentration and the presence of ADA appears to have the greatest utility 3 . Canterbury Health Laboratories, New Zealand (CHL) has developed a competitive binding ELISA to detect neutralising antibodies whereas most commercial assays utilise a bridging methodology Objectives: Compare performance of a competitive binding assay with two commercial bridging assays in the detection of ADA to anti-TNFα biodrugs in serum samples with low/absent biodrug concentration Methods: Serum samples referred for anti TNF biodrug concentrations found to have very low/undetectable concentrations (<1mg/l) were tested for ADA using the competitive-bind assay and two bridging assays (TANI Medikal and GRIFOLS) Results: Over a 22 month period (Jan 2014 – Oct 2016), 67% (331/497) of referred samples had biodrug concentrations below 7mg/l and 15% (n=79) had low/undetectable biodrug concentrations (adalimumab n=36 or infliximab n=43). ADAs were detected in 53% (42/79) of this latter group. The competitive binding assay detected ADAs in all samples testing positive for ADA by binding assay. In addition a further 8 samples were positive for ADA by the competitive assay: 53% (42/79) positive for ADA by the competitive assay and 33% positive by one or other of the commercial assays Conclusions: The competitive binding ELISA was more sensitive in detecting biodrug ADAs in serum samples with very low/undetectable biodrug concentrations References: Felice C, Marco M, Pugliese D, et al. Expert Opin Biol Ther 2015;15:1107–1117. Schaeverbeke T, Truchetet M, Kostine M, Barnetche T et al. Rheumatology 2016;55:210–220. Jani M, Chinoy, Warren R, et al. Arthritis and Rheumatology 2015;67:2011–2019. Disclosure of Interest: None declared